Continuous Effects of Green Transformational Leadership and Green Employee Creativity: A Moderating and Mediating Prospective - Sidney, Mangenda Tshiaba; Wang, Nianxin; Nazir, Mehrab; Ferasso, Marcos; Saeed, Abeera (Frontiers in Psychology, 2022)
Responding to environmental concerns is a new indication of innovativeness, allowing businesses to achieve competitive advantages by executing innovative activities that benefit individuals and the entire community. Much intention has been retained in this perspective on “green employee creativity.” However, few studies have examined the combined effect of green creativity from relations between people and organizational practices. As a result, we sought to explain the variation in employees' green creativity by investigating relations of four factors outside of the organizational context (transformational leadership, green innovation strategy, green human resources management - GHRM and green process engagement) with individual factors (such as employees' green creativity). Data were retrieved from 150 employees pertaining to electronic companies. Data were statistically analyzed by SmartPLS software. Main results revealed that green transformational leadership positively affects employee green creativity, and GHRM and green process engagement play a significant mediating role in the relation between green transformational leadership and employee green creativity. Furthermore, the green innovation strategy plays a significant role moderating the green transformation leadership and green process engagement. This effect is improved when the level of green innovation strategy is high rather than low. Keywords: Green human resources management; Green process engagement, Green creativity; Green transformational leadership; Green innovation strategy.